A cultural historical activity theory analysis of educational psychologists' statutory assessment process post- 2014 children and families act. Issue 4 (2nd October 2022) - Capper, Zoe; Soan, Colette
ABSTRACT: The activity of educational psychologists' (EPs') statutory psychological assessment continues to be viewed critically within literature. The current research explores the understanding of EPs and special educational needs and disability (SEND) officers in this activity, considering the 2014/2015 policy reforms. Semi-structured interviews were conducted in a single Local Authority (LA) using Cultural Historical Activity Theory (CHAT) to explore the constructions of each group. Identified contradictions within the data were explored within a Development Work Research (DWR) Lab to create shared actions. Over time, EPs' practice has remained constant in its recognised strengths, but identified contradictions within historic literature remained evident. Actions moving forward sought to redevelop graduated assessment processes, promote stronger multi-professional working, strengthen annual review processes, and create effective methods for efficient data collection.